2020
DOI: 10.12688/f1000research.21007.2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive statistical model for the factors associated with prenatal depression among pregnant adolescents in Maha Sarakham province, Thailand

Abstract: Background: The rate of adolescent pregnancy has steadily increased in Thailand over the years and depression is considered an important psychological problem in many pregnant adolescents. The aims of this study were to determine the proportion of pregnant adolescents with depressive symptoms and to identify a predictive statistical model for the factors related to prenatal depression among adolescents at antenatal care clinics in 10 community health centers in Maha Sarakham Province. Methods: A cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For example, in a study of rural pregnant women in KwaZulu-Natal, South Africa, 47% of the women showed positive signs of depression, and 45% of those who were depressed were HIV-positive [33]. Uthaipaisanwong et al [26], recorded 46% whilst a 43.9% prevalence was found by a study conducted on prenatal depression among pregnant adolescents in the Maha Sarakham province [35]. In Ghana, one study found a point prevalence of 69.9.% among mothers with sick infants in Kumasi and currently the highest prevalence of depression in the country [4].…”
Section: Prevalence Of Antepartum Depression Among Adolescent Pregnan...mentioning
confidence: 99%
“…For example, in a study of rural pregnant women in KwaZulu-Natal, South Africa, 47% of the women showed positive signs of depression, and 45% of those who were depressed were HIV-positive [33]. Uthaipaisanwong et al [26], recorded 46% whilst a 43.9% prevalence was found by a study conducted on prenatal depression among pregnant adolescents in the Maha Sarakham province [35]. In Ghana, one study found a point prevalence of 69.9.% among mothers with sick infants in Kumasi and currently the highest prevalence of depression in the country [4].…”
Section: Prevalence Of Antepartum Depression Among Adolescent Pregnan...mentioning
confidence: 99%